2013
DOI: 10.1007/s10071-013-0715-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of personality, age, sex, and estrous state on chimpanzee problem-solving success

Abstract: Despite the importance of individual problem solvers for group- and individual-level fitness, the correlates of individual problem-solving success are still an open topic of investigation. In addition to demographic factors, such as age or sex, certain personality dimensions have also been revealed as reliable correlates of problem-solving by animals. Such correlates, however, have been little-studied in chimpanzees. To empirically test the influence of age, sex, estrous state, and different personality factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
69
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 85 publications
1
69
1
Order By: Relevance
“…An analysis of the linkage between personality traits and performance in cognitive tasks in animals has recently started and to date some results are available across species (e.g. Benus et al 1987;Hopper et al 2014;Tebbich et al 2012;Verbeek et al 1994). …”
Section: Introductionmentioning
confidence: 98%
“…An analysis of the linkage between personality traits and performance in cognitive tasks in animals has recently started and to date some results are available across species (e.g. Benus et al 1987;Hopper et al 2014;Tebbich et al 2012;Verbeek et al 1994). …”
Section: Introductionmentioning
confidence: 98%
“…It is somewhat surprising that we did not find evidence that age had an effect upon social learning, given the evidence that young individuals undergo an enhanced “sensitive period” in social learning behaviour (Biro et al 2003) and elderly individuals decline in social cognition (Lacreuse et al 2014, although see; Hopper et al 2014). Perhaps while there may be an early sensitive period in chimpanzees’ proclivity for social learning, once passed, social learning may remain relatively stable over the rest of their lives.…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, wild baboons that were scored most highly on ‘boldness’ or ‘anxious’ traits were found to show a greater improvement on a foraging task after observing a demonstrator (Carter et al 2014). In addition, Hopper et al (2014) found that certain chimpanzee personality traits (‘methodical’, ‘openness’ and ‘dominance’) are associated with success in asocial learning paradigms. Examining personality in parallel with performance across a broad range of social learning tasks would be useful in exploring how proclivity for social information use fits into the broader tapestry of chimpanzee personality traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, studies of nonhuman primate species show that they have stable, consistent personalities (Massen et al, 2013; Morton et al, 2013; for a review in nonhuman primates see Freeman & Gosling, 2010), which also correlate with their responses in behavioural experiments (e.g. Hopper, Price, et al, 2014; Massen et al, 2013). The personality dimensions that have been identified to apply to nonhuman primates include some dimensions that are more social (e.g.…”
mentioning
confidence: 99%